Seznam praprotnic in semenk ter njihova nahajališča na Slovenskem v delih Franca Ksaverja Wulfena - Praprotnik, Nada (Scopolia, 2016)
Franc Ksaver Wulfen (1728-1805) was a natural historian engaged in mineralogy, botany and zoology. He studied the flora of Slovenia (Carniola) in 1755 and 1761 when living in Gorizia, and in the 1762-1763 period when residing in Ljubljana. He was botanical mentor to Karl Zois and Franc Hladnik. In his botanical works he listed 197 localities of vascular plants for 957 taxa. He described 12 new vascular plant species for the territory of Slovenia, six of which are still valid according to the current criteria of plant systematics. The localities of vascular plants are given herewith, as well as a list of localities with taxa and a full list of the names used by Wulfen for the plants from Slovenian territory, together with the currently valid names.
Keywords: biografije; biography; botanika; history; history of botanical research; lists; praprotnice; Rhododendron-Park Bremen; semenke; seznami; Slovenia; Slovenija; vascular plants; Wulfen, Franc Ksavec, 1728-1805; zgodovina; zgodovina botaničnih raziskovanj